Optimum Use of Renewable Energy Resources to Generate Electricity via Hybrid System - Bhuiyan, Mahmud Abdul Matin; Mandal, Anand; Thakur, Ujwal Kumar (Kathmandu University Journal of Science Engineering and Technology, 2013)
The necessity of a hybrid energy system is gaining more importance day by day as it incorporates two or more renewable energy resources that, when integrated, overcome limitations inherent in either. A hybrid energy system has been seen as an excellent solution for the electrification of rural places where grid extension is difficult and economically not feasible. Such systems may consist of several renewable resources such as solar PV, wind, biomass, micro-hydro, geothermal, and other conventional generators for backup, where the deficiency of one system can be compensated by others. This paper depicts the different system components and their optimal combination for the efficient generation of electrical energy exploiting locally available resources. The model discussed in the paper comprises micro-hydro, solar PV, and biomass for the rural village in Nepal known as Kalikhola, which is used as a case study. The optimized hybrid system shows a unit cost of $0.088/KWh, which is obtained after the simulation considering the contribution of individual renewable resources participating in the system.